From west to east: Heterogeneity in the life history traits of a small pelagic fish (Sardina pilchardus) throughout the Mediterranean - Caballero-Huertas, Marta; Frigola-Tepe, Xènia; Viñas, Jordi; Muñoz, Marta (Frontiers in Marine Science, 2023)
Small pelagic fish are key elements of the marine trophic network ecosystem and are of great importance with respect to the total landing of marine species. Over the last decades, a decrease in biomass and catches of European sardine has been described, especially in the Mediterranean Sea, as an indication of a drop in the stocks' condition. Multiple causes, among them direct and indirect anthropogenic factors, seem to be converging and affecting to this species. To address this issue, it is important to identify the current variability in sardine s' health status and understand the strategies for energy allocation, which are intimately related to the reproductive potential and recruitment success. We analyzsed the somatic condition through tissue and mesenteric lipid measurements, relative condition (Kn) and hepatosomatic (HSI) indices, and gonadosomatic index (GSI) in four subareas of the Mediterranean (Alboran, Northern Spain, Northern Adriatic, and Aegean Sea) and of an outgroup from the Atlantic. The analyses were performed within the gonadal development framework cycle since the translocation to reproduction may mask the state of actual energy reserves for comparison. Results revealed marked differences in health status among subareas, highlighting the low condition of the Northern Spain sardines throughout the annual cycle. The uniform condition throughout gonadal development in the Northern Adriatic suggests that resources availability modulates the reproductive strategy not behaving as a strict capital breeder. Moreover, similarities between Alboran and Atlantic stocks are discussed, highlighting the marked energy replenishment of the latter after reproduction compared to the Mediterranean stocks. The Aegean stock was the fastest to reach its maximum after spawning, presenting low condition values from the developing to actively spawning period, but with the greatest recovery at the regressing phase, coinciding with a peak in productivity. Finally, the role of the liver in sardine 's energy storage is analyzsed considering stocks' heterogeneity, potentially indicating that HSI is intimately related to feeding activity. Given the divergences among stocks, we propose concrete measures for the managingement of thise resource throughout this important water body(i.e., the need for adapting the close seasons), which could be applied to other species in similar contexts.